Assessment of initiation of post-exposure prophylaxis with anti-rabies vaccine in cases of dog bites: an observational study - Ramanand, Jaiprakash B.; Jaykare, Swapnil Chudaman; Ramanand, Sunita J.; Zende, Ajitkumar M.; Bhosale, Rama R.; Patil, Jyoti R. (International Journal of Basic & Clinical Pharmacology, 2017)
Background: The management of rabies is challenging because of the long incubation period, lack of specificity of early prodromal symptoms and 100% fatality rate. Post-exposure prophylaxis (PEP) with anti-rabies vaccine (ARV) at the earliest has proven life-saving. Studies conducted in many parts of the country have shown that the time interval between exposure and initiation of PEP is wide. The objective was to study the profile of dog bites cases and assess initiation of PEP with ARV. Methods: Prospective observational study where prescription sheets of all new cases of dog bite injury were evaluated for a period of 3-month. Results: The victims of dog bite were predominantly males (72.41% males vs. 27.59% females, n=551). 45% cases belonged to the age group of 15-44 years. The majority of the cases (88.03%) were of wound Category II. The most common site of a dog bite was lower limb (80.94%). The percentage of cases who had received ARV within 24 hrs was 41.92, between 1 and 3 days was 31.03, between 4 and 10 days was 21.60, whereas 5.45% cases received vaccine after 10 days of exposure. Conclusion: Substantial proportion of victims of dog bite did not report and receive PEP within 24 hrs of exposure.